Bibliometric Analysis of Voluntary Corporate Internet Reporting - Muhammad Rifqi Arif Munandar; Rahmawati Rahmawati; Sri Hartoko; Endang Dwi Amperawati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The present research aims to identify the major research trends, influential contributors, and emerging themes in Internet Financial Reporting (IFR) research while proposing directions for future investigations. The growing adoption of digital technologies has encouraged organizations to disclose financial and sustainability information through internet-based platforms, making IFR an increasingly important area of academic inquiry. Method: A bibliometric analysis was conducted using 970 publications indexed in the Scopus database covering the period from 2015 to 2024. The analysis employed performance analysis and science mapping techniques, including citation analysis, co-authorship analysis, co-citation analysis, and keyword co-occurrence analysis. Network visualization was performed to reveal collaboration patterns, intellectual structures, and thematic evolution within the IFR literature. Results: The findings identify the most productive and influential authors, institutions, countries, and publications based on citation and publication performance. Keyword co-occurrence analysis revealed six major research clusters representing the dominant themes in IFR studies, while co-authorship analysis identified collaboration networks involving 28 authors. The results also demonstrate the evolution of research interests, highlighting emerging topics related to digital reporting, transparency, sustainability reporting, and technological innovation. Novelty: The bibliometric investigation provides a comprehensive overview of Internet Financial Reporting research by mapping its intellectual structure, identifying knowledge gaps, and outlining promising future research directions. The findings serve as a valuable reference for researchers and practitioners seeking to advance the development of IFR in the era of digital transformation.